Impact attenuation of user-centred bicycle helmet design with different foam densities. (January 2019) - Mustafa, H; Pang, T Y; Ellena, T; Nasir, S H
Abstract: One possible solution to overcome helmet fit problem for each user is the customized "user-centred" or "subject-specific" helmet design approach. This study sets out to determine the effect of the user-centred helmet design with different foam density (from 50 kgm −³ to 100 kgm −³ ) on the impact attenuation of the bicycle helmet. A user-centred helmet was designed to follow the shape of the individual head shape of a participant. Reverse engineering method was applied to obtain the digital models. A validated finite element simulation model of the drop impact of bicycle helmet was used to test the impact attenuation. It was found that the user-centred helmet HP1 recorded a significant improvement in HFI when compared to the original helmet A clear difference was observed for each helmet at different density values at all locations, especially between an EPS density of 64 kgm −³ and 100 kgm −³ . In addition, a similar pattern of PLA versus density curves was also observed at each impact location.